Pendampingan Program Peduli Lingkungan Habitat Bulus pada Karang Taruna Ketawang Tawun Jaya - Betty Prastiwi; Bella Mustikasari; Jiman; Sudarto; Sugiharto (Jurnal Abdikarya Pembangunan, 2022)
The program of Karang Taruna Ketawang activities is still not able to The Karang Taruna Ketawang activity program is still unable to solve the problem of plastic waste that interferes with the preservation of the Asiatic Softshell Turtle habitat in Tawun. It is necessary to assist in the bulus habitat environmental care program starting from the planning stage to its implementation. This service uses the Participated Action Research method. Problem mapping and action formulation are carried out jointly between Karang Taruna and the service team. This program consists of delivering environmental materials on the dangers of plastic waste for the Asiatic Softshell Turtle habitat and real action on the laying of trash bins in strategic locations. This program was attended by 13 residents who showed an increase in environmental concern for bulls' habitat. Based on questionnaire data, there was a 46% increase in residents who stated that they disposed of garbage in their place and a 54% increase in residents who stated that they were compact with other residents in protecting the environment. Knowledge of plastic waste encourages an increase in cohesiveness in protecting environmental habitats, while the provision of trash cans encourages residents to dispose of waste in its place. Program kegiatan Karang Taruna Ketawang masih belum mampu menyelesaikan masalah sampah plastik yang mengganggu kelestarian habitat Bulus di Tawun. Perlu adanya pendampingan program peduli lingkungan habitat Bulus mulai dari tahap perencanaan hingga pelaksanaannya. Pengabdian ini menggunakan metode Participated Action Research. Pemetaan masalah dan perumusan aksi dilaksanakan bersama antara Karang taruna dan Tim Pengabdi. Program ini terdiri dari Penyampaian materi lingkungan tentang bahaya sampah plastik bagi habitat Bulus dan aksi nyata peletakan tempat sampah di lokasi strategis. Program ini diikuti 13 warga yang menunjukkan adanya peningkatan kepedulian lingkungan terhadap habitat Bulus. Berdasarkan data kuesioner terdapat peningkatan 46% pada warga yang menyatakan membuang sampah pada tempatnya dan peningkatan 54% pada warga yang menyatakan kompak dengan warga lainnya dalam menjaga lingkungan habitat bulus. Pengetahuan tentang sampah plastik mendorong adanya peningkatan kekompakan menjaga habitat lingkungan, Sedangkan penyedian tempat sampah mendorong warga untuk membuang sampah pada tempatnya.